Narcissistic Personality Disorder In The Novel Best Day Ever By Kaira Rouda - Warham, Warham; Moelier , Dahlia D.; Abeng, Andi Tenri (Humaniora: Journal of Linguistics, Literature, and Education, 2024)
This study aimed to identify the causes and types of narcissistic personality disorder in the main character of Kaira Rouda's novel, "Best Day Ever" and hoped to provide a foundation for further research in this area. The data source for this study was the novel itself. Qualitative descriptive research methods were used to analyse the data with a psychological approach, including the techniques of reading, note-taking, and analysis. Caligor et al’s and Bursten's theories were used to classify the data. The results of this study reveal that the main character was a narcissist. he had 8 out of 9 signs of narcissistic personality disorder caused by excessive self-importance, fantasies of success, feelings of being special, excessive need for admiration, arrogance, and lack of empathy, and the main character's narcissistic personality disorder was predominantly of the manipulative type